Characterization of the Replication, Maintenance, and Transfer Features of the IncP-7 Plasmid pCAR1, Which Carries Genes Involved in Carbazole and Dioxin Degradation - Shintani, Masaki (American Society for Microbiology, 2006)
Isolated from Pseudomonas resinovorans CA10, pCAR1 is a 199-kb plasmid that carries genes involved in the degradation of carbazole and dioxin. The nucleotide sequence of pCAR1 has been determined previously. In this study, we characterized pCAR1 in terms of its replication, maintenance, and conjugation. By constructing miniplasmids of pCAR1 and testing their establishment in Pseudomonas putida DS1, we show that pCAR1 replication is due to the repA gene and its upstream DNA region. The repA gene and putative oriV region could be separated in P. putida DS1, and the oriV region was determined to be located within the 345-bp region between the repA and parW genes. Incompatibility testing using the minireplicon of pCAR1 and IncP plasmids indicated that pCAR1 belongs to the IncP-7 group. Monitoring of the maintenance properties of serial miniplasmids in nonselective medium, and mutation and complementation analyses of the parWABC genes, showed that the stability of pCAR1 is attributable to the products of the parWAB genes. In mating assays, the transfer of pCAR1 from CA10 was detected in a CA10 derivative that was cured of pCAR1 (CA10dm4) and in P. putida KT2440 at frequencies of 3 × 10(−1) and 3 × 10(−3) per donor strain, respectively. This is the first report of the characterization of this completely sequenced IncP-7 plasmid.